STRATEGI PUSTAKAWAN DALAM PELESTARIAN BAHAN PUSTAKA - Evalina Evalina (UIN Imam Bonjol Padang, 2019)
Abstract : The library has the task as a provider of library materials that must continue to be developed, this development has an influence on the needs of users who continue to surge. The development of library materials also influences the amount of library materials collected, of course, from year to year the collection continues to develop. The strategy undertaken by librarians / library officers in preserving library materials is the existence of preventive actions from librarians in the form of physical preservation activities such as granting camphor, fimigation, and prevention of damage from humans and preservation of information in the form of media transfer and curative measures, namely the existence of binding activities, and granting. To carry out the strategy of preservation of library materials there are obstacles faced, among others, the lack of Human Resources / HR in quality and quantity as well as facilities and infrastructure that are still not maximal in supporting the implementation of library preservation activities. the preservation carried out is not only related to technical issues, and the facilities used can be more adequate to support the implementation of conservation activities in the future to be of higher quality.Keyword : Strategy, Preservation of Library MaterialsAbstrak : Perpustakaan mengemban tugas sebagai penyedia bahan pustaka yangharus terus dikembangkan, pengembangan inilah yang berpengaruh terhadap kebutuhan pemustaka yang terus melonjak. Pengembangan bahan pustaka juga berpengaruh terhadap banyaknya bahan pustaka yang dikoleksi, tentunya dari tahun ke tahun koleksi terus berkembang Strategi yang dilakukan oleh pustakawan/ petugas perpustakaan dalam pelestarian bahan pustaka yaitu adanya tidakan preventif dari pustakawan berupa kegiatan terhadap pelestarian fisik seperti pemberian kapur barus, fimigasi, dan pencegahan terhadap kerusakan dari manusia dan pelestarian informasi berupa alih media serta tindakan kuratif yaitu adanya kegiatan penjilidan, dan penyampulan. Untuk menjalankan srategi pelestarian bahan pustaka ada kendala yang dihadapi antara lain kurangnya Sumber Daya Manusia/SDM dalam kualitas dan kuantitas serta sarana dan prasarana yang ada masih belum maksimal dalam menunjang pelaksanaan kegiatan pelestarian bahan pustaka diharapkan di perpustakaan ada memiliki spesialis untuk bidang pelestarian sendiri agar kegiatan pelestarian yang dilakukan tidak hanya berhubungan dengan masalah teknis, serta fasilitas yang digunakan dapat lebih memadai untuk menunjang pelaksanaan kegiatan pelestarian kedepannya agar lebih berkualitas.Kata Kunci : Strategi, Pelestarian Bahan Pustaka